Clinical characteristics and prognosis of myelin oligodendrocyte glycoprotein antibody-seropositive paediatric optic neuritis in China. Issue 6 (26th July 2018) - Song, Honglu; Zhou, Huanfen; Yang, Mo; Tan, Shaoying; Wang, Junqing; Xu, Quangang; Liu, Hongjuan; Wei, Shihui
Abstract : Background/Aims: To investigate clinical characteristics and prognosis of paediatric optic neuritis (PON) in patients seropositive for myelin oligodendrocyte glycoprotein antibody (MOG-Ab) in China. Methods: Children displaying initial onset of optic neuritis (ON) were recruited from the Neuro-ophthalmology Department in the Chinese People's Liberation Army General Hospital from January 2016 to August 2017. They were assigned into three groups based on antibody status: MOG-Ab-seropositive ON (MOG-ON), aquaporin-4 antibody-seropositive ON (AQP4-ON) and double seronegative ON (seronegative-ON). Results: Totally 48 patients were assessed, including 25 MOG-ON (52.1%), 7 AQP4-ON (14.6%) and 16 seronegative-ON (33.3%). The MOG-ON and seronegative-ON cohorts had equal ratios of female/male, but the AQP4-ON cohort was predominantly females (100%). The patients with MOG-ON were significantly younger at onset compared with the AQP4-ON group. Of the MOG-ON eyes, 97.6% had good recovery of visual acuity (VA) (≥0.5) compared with33.3% of AQP4-ON eyes (p<0.001). However, there was no significant difference compared with the seronegative-ON eyes (82.6%, p = 0.052). Two children in the MOG-ON group ended up being diagnosed with acute disseminated encephalomyelitis, while only one patient in the AQP4-ON group developed neuromyelitis optica during follow-up. Patients with MOG-ON had thicker peripapillary retinal nerve fibre layers overall and in the superior and inferior quadrants than in patients with AQP4-ON (p = 0.005, p = 0.002 and p = 0.024, respectively). In addition, the macular ganglion cell-inner plexiform in MOG-ON eyes became significantly thicker than in AQP4-ON eyes (p=0.029). Orbital MRI revealed a larger proportion of patients with MOG-ON had intracranial optic nerve involvement than patients with seronegative-ON (51.2% vs 17.4%, p = 0.009). Conclusion: MOG-ON was the most common PON subtype in China. MOG-ON had different clinical features including earlier age of onset, equal female/male ratio, better recovery of VA and thicker peripapillary retinal nerve fibre and macular ganglion cell-inner plexiform layers. MOG-Abs may be a potential biomarker for determining visual prognosis with PON.